Higher courses as the first higher school in Lithuania - Česlovas Mančinskas (Lietuvos Istorijos Studijos)
After the newly independent Lithuanian state had been established, the necessity of development of economics, education, culture, and the state governing machinery became obvious. So the society needed a sufficient amount of educated specialists, which, at this moment, especially with a higher education, had only been a few. Because of the Russian tsarist governmental politics of national oppression, and having no higher school, the country remained undeveloped for almost a century. According to the data of the first general census of the population, only 42.18% of the population of Lithuania were literate, 25.18% were half-literate, and the others were illiterate persons.